Investigation of Plasma Inflammatory Profile in Diabetic Patients With Abdominal Aortic Aneurysm: A Pilot Study. (November 2018) - Lareyre, Fabien; Moratal, Claudine; Chikande, Julien; Jean-Baptiste, Elixène; Hassen-Khodja, Réda; Neels, Jaap; Chinetti, Giulia; Raffort, Juliette
Introduction: Clinical studies have unraveled a negative association between diabetes and abdominal aortic aneurysm (AAA), but the mechanisms involved are still poorly understood. The aim of this study was to determine whether diabetic patients with AAA had a distinct plasma inflammatory profile compared to nondiabetic patients. Methods: Plasma samples were obtained from 10 diabetic patients with AAA and 10 nondiabetic patients with AAA. The relative protein expression of 92 inflammatory-related human protein biomarkers was assessed by proximity extension assay technology using Proseek Multiplex Inflammation I kit (Olink). Results: Clinical characteristics were similar in diabetic patients with AAA compared to nondiabetic patients with AAA, the median ages being 67 and 73 years, respectively ( P = .61). The AAA diameters were, respectively, 50 and 49 mm ( P = .72). Among the 92 markers screened, 67 (72.8%) were detected in all samples. Diabetic patients had significantly lower protein expression of C-C motif chemokine 19 (CCL19) and C-C motif chemokine 23 (CCL23; 542.3 vs 980.3, P = .01 and 1236 vs 1406, P = .04, respectively). They tended to have higher expression of tumor necrosis factor ligand superfamily member 14 (TNFSF14) compared to controls (14.6 vs 10.8, P = .05). Conclusion: Diabetic patients with AAA differentially expressed CCL19, CCL23 and TNFSF14 in plasma compared to nondiabetic patients with AAA. Further studies are required to determine whether the markers identified could play a role in the negative association between diabetes and AAA pathogenesis.